THE ANALYSIS OF INDONESIAN AFFIXES IN ENGLISH WORDS IN “23 TUTORIAL MENGGAMBAR DENGAN INKSCAPE” E-BOOK - Muhammad Rofiddin; Yayan Suryana; Yuniarti Yuniarti (Indonesian Journal of Learning and Instruction, 2023)
This study aimed to examine the combination of Indonesian affixes with English base words and explore their meanings. Using a qualitative research method, specifically document analysis, the research focused on data collected from the e-book titled "23 Tutorial Menggambar dengan Inkscape". Following Creswell's procedures for data collection and analysis, English words accompanied by Indonesian affixes were selected as the data. The analysis involved categorizing the data into morpheme types, identifying patterns, and determining their meanings. The findings revealed that English base words can be combined with Indonesian affixes. The identified patterns included Indonesian prefix + verb, Indonesian prefix + noun, noun + Indonesian suffix, and Indonesian prefix + verb + Indonesian suffix. Besides, Indonesian affixes also can change the word class of English base words and their meaning. This research sheds light on the utilization of Indonesian affixes in English words, contributing to our understanding of code-switching at the morphemic level.Keywords: world englishes; code-switching; morphology; Indonesian affixes; English words